Project experiences and internships in public health: nursing academic perspective - Cristiano Batista Gonçalves, Nayra Samanta Alves Luz, Izabel Cristina Falcão Juvenal Barbosa (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v5i4.5276